Procalcitonin Read Outside Its Derivation Population and an Antibiotic Course Ended by the Calendar: A Late Preterm Neonate with Transient Tachypnoea of the Newborn Managed as Probable Early-Onset Sepsis - Deril Ridwan; Eny Yantri; Benny Sana Putra (Scientific Journal of Pediatrics, 2026)
Background: Respiratory distress in a late preterm neonate forces an early choice between transient tachypnoea of the newborn and pneumonia with early-onset sepsis, usually before any confirmatory result exists. Objective: To audit how biomarkers and an antibiotic stop rule were interpreted in a late preterm neonate managed as probable early-onset sepsis. Methods: This CARE-guided case report reviewed the de-identified clinical record, re-read each test against its derivation population, and recomputed clinical, respiratory, bilirubin, fluid, nutrition, and dosing quantities. Results: A 36-week male neonate weighing 3,000 g was born after prolonged preterm premature rupture of membranes with oligohydramnios and grunted from birth. Continuous positive airway pressure began at one minute; oxygen returned to room air by five minutes and support ended on day 3. The full blood count was normal for age, C-reactive protein fell from 28 to 11 mg/L, and a bacterial polymerase chain reaction was negative, yet a five-day antibiotic course was completed. Procalcitonin of 6.8 ng/mL was interpreted outside the population from which its reference interval was derived, and the stop rule depended on a culture result that never arrived. Conclusion: Neonatal biomarkers should be interpreted against age- and physiology-matched populations, and antibiotic stop rules should execute after a defined interval unless the culture signals. A twelve-item minimum data set is proposed.